2015
DOI: 10.1111/ap.12126
|View full text |Cite
|
Sign up to set email alerts
|

“Going the Extra Mile”: Satisfaction and Alliance Findings from an Evaluation of Videoconferencing Telepsychology in Rural Western Australia

Abstract: Objective: Technology is changing how we behave, communicate, and process information, and this has significant implications for mental health care. Telepsychology has appeal as a solution to obstacles of distance and access in rural and regional areas; however, few services appear to provide telepsychology as a routine service component for psychotherapeutic exchanges. The primary research goal of a multi-year PhD project was to explore and explain the disconnect between research and practice in telepsycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 50 publications
(55 reference statements)
3
46
1
2
Order By: Relevance
“…Similar to previous studies, clients found that once they became immersed in the therapy itself, the technology became less of a focus (Mallen et al, 2005). This has been a recurring theme in online therapy literature, providing strong evidence that the experience of receiving therapy through videoconferencing is not subpar to that of face-to-face therapy, but instead "different" (Day and Schneider, 2002;Lewis et al, 2004;Simpson et al, 2005;Richardson et al, 2015).…”
Section: Discussionsupporting
confidence: 61%
“…Similar to previous studies, clients found that once they became immersed in the therapy itself, the technology became less of a focus (Mallen et al, 2005). This has been a recurring theme in online therapy literature, providing strong evidence that the experience of receiving therapy through videoconferencing is not subpar to that of face-to-face therapy, but instead "different" (Day and Schneider, 2002;Lewis et al, 2004;Simpson et al, 2005;Richardson et al, 2015).…”
Section: Discussionsupporting
confidence: 61%
“…Some have indicated that they would use it if the need arose. So a new opportunity for therapeutic connection has been established, and its success and challenges seem consistent with existing literature on the acceptability of telepsychology to clients and on the surprisingly limited impact of the ever‐present technological “bugs” (Backhaus et al., ; Richardson, ; Richardson et al., ; Richardson, Reid, & Dziurawiec, in press; Shandley et al., ; Simpson, ; Simpson, Bell, Knox, & Mitchell, ; Simpson & Reid, , ).…”
Section: Novel Application Of “Traditional” Telepsychology: Individuasupporting
confidence: 61%
“…Their work demonstrates that telepsychology is acceptable to rural patients and offers a strong proof of concept for how such a clinic can be developed and implemented in parallel to traditional in‐person services. Richardson, Reid, and Dziurawiec () address many of the perceived shortcomings of telepsychology from a provider's perspective, systematically demonstrating how a strong therapeutic alliance can be achieved and maintained in telepsychology practice.…”
Section: This Special Issuementioning
confidence: 99%